Research Competency among Elementary School Teachers: An evaluative assessment for School-Based Action Research (SBAR) - Cagaanan, John Clyde A.; Gosadan, Beatriz D. (JPAIR Institutional Research, 2018)
Teachers have been challenged to become professionally productive through research outputs. DepEd Memorandum no.114 s. 2014 mandated the teachers to conduct action research or assessment within their realm. A yearly congress for School-Based Action Research (SBAR) was done. However, the lack of research output remains a problem in every school district. This study aimed to determine the level of research competency among the elementary school teachers in Makilala West and Makilala Central Districts, Cotabato Division. Anchored on Corey's Theory on Curriculum Development and Research and Lewin's Theory on Research, this study employed a mixed method design. On the quantitative strand, 114 elementary classroom teachers were the respondents while 16 schools participated in the qualitative strand of the study. Following the merging of the data, the quantitative and qualitative data showed divergence. Results revealed that the respondents were moderately competent in research. Digging on the problems encountered by the teachers for not conducting any research activity, the findings exposed that the poor background of teachers in research, the problem on schedule, overlapping of activities, and too much administrative work were the reasons behind their failure to submit their research output. To aid teachers in the preparation of scholarly research, an intervention plan was made.
Keywords: Action Research; competency; intervention plan; mixed method; Philippines